Pediatric Transport Triage: Development and Assessment of an Objective Tool to Guide Transport Planning. Issue 5 (May 2020) - Steffen, Katherine M.; Noje, Corina; Costabile, Philomena M.; Henderson, Eric; Hunt, Elizabeth A.; Klein, Bruce L.; McMillan, Kristen Nelson
Abstract : Objectives: We developed a Pediatric Transport Triage Tool (PT3) to objectively guide selection of team composition and transport mode, thereby standardizing transport planning. Previously, modified Pediatric Early Warning Score for transport has been used to assess illness severity but not to guide transport decision making. Methods: The PT3 was created for pediatric transport by combining objective evaluations of neurologic, cardiovascular, and respiratory systems with a systems-based medical condition list to identify diagnoses requiring expedited transport and/or advanced team composition not captured by neurologic, cardiovascular, and respiratory systems alone. A scoring algorithm was developed to guide transport planning. Transport data (mode, team composition, time to dispatch, patient disposition, and complications) were collected before and after PT3 implementation at a single tertiary care center over an 18-month period. Results: We reviewed 2237 inbound pediatric transports. Transport mode, patient disposition, and dispatch time were unchanged over the study period. Fewer calls using a transport nurse were noted after PT3 implementation (33.9% vs 30%, P = 0.05), with a trend toward fewer rotor-wing transports and transports requiring physicians. The majority of users, regardless of experience level, reported improved transport standardization with the tool. Need to upgrade team composition or mode during transport was not different during the study period. No adverse patient safety events occurred with PT3 use. Conclusions: The PT3 represents an objective triage tool to reduce variability in transport planning. The PT3 decreased resource utilization and was not associated with adverse outcomes. Teams with dynamic staffing models, various experience levels, and multiple transport modes may benefit from this standardized assessment tool. Abstract : Supplemental digital content is available in the text.